Hubungan Define dan Measure Terhadap Pencegahan Ulkus Dekubitus pada Pasien dengan Gangguan Mobilitas Fisik : Penelitian - Moh. Iksan; Elin Hidayat; Bayu Eka Kurniawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Decubitus ulcers are wounds caused by prolonged pressure on the skin, in patients with limited mobility. The aim of this study was to analyze the relationship between Define and Measure on the prevention of decubitus ulcers in patients with physical mobility disorders at Undata Regional General Hospital, Central Sulawesi Province. Method: This study is quantitative with a cross-sectional approach, using an analytical observational design. The population in this study were 52 nurses in the Bougenville ward, ICU, and ICVCU. The sampling technique used was Proportional Stratified Random Sampling. Research Results: The results of the study from 52 respondents showed that there was no significant relationship between nurses' Define and the prevention of decubitus ulcers in patients with impaired physical mobility (Monte Carlo test, p = 0.051), there was a significant relationship between nurses' Measure and the prevention of decubitus ulcers in patients with impaired physical mobility (Monte Carlo test, p = 0.007). Conclusion: It was concluded that the nurse's Measure factor was significantly related to efforts to prevent decubitus ulcers, while the Define factor did not show a significant relationship. Suggestion: Nurses are expected to improve their understanding and application of the Define and Measure aspects in decubitus ulcer prevention. In general, increased knowledge, training, and ongoing evaluation are essential to optimize decubitus ulcer prevention efforts in patients with impaired physical mobility.